Exciton Coupling Model for the Emergence of Second Harmonic Generation from Assemblies of Centrosymmetric Molecules - Snyder, Gregory R. (American Chemical Society, 2014)
[Image: see text] A simple model is presented for interpreting the presence of substantial second harmonic generation (SHG) activity from assemblies of centrosymmetric molecular building blocks. Using butadiene as a computationally tractable centrosymmetric model system, time-dependent Hartree–Fock calculations of the nonlinear polarizability of butadiene dimer were well-described through exciton coupling arguments based on the electronic structure of the monomer and the relative orientation between the monomers within the dimer. Experimental studies of the centrosymmetric molecule 2,6-di-tert-butylanthraquinone suggest the formation of a combination of SHG-active and SHG-inactive crystal forms. The structure for the centrosymmetric form is known, serving as a negative control for the model, while the presence of an additional SHG-active metastable form is consistent with predictions of the model for alternative molecular packing configurations.